TINGKAT KESESUAIAN KURIKULUM SMK TATA KECANTIKAN RAMBUT DITINJAU DARI KOMPETENSI YANG DIBUTUHKAN DUNIA USAHA/ DUNIA INDUSTRI - Megasari, Dindy Sinta; Nurlaela, Luthfiyah; Munoto, Munoto (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2014)
Abstrak Curriculum used and developed by Vocational High School should already be relevant to the need of business or industry world (DU/DI). The purposes of this research are 1) To know the conformity level of curriculum according to the need of DU/DI at the productive training education technique of hair beauty; 2) To describe the demand of DU/DI to students of hair beauty; 3) To describe curriculum implementation of productive training education technique of hair beauty; 4) To describe the demand of the students of hair beauty to technology development in hair beauty business. The research was performed at SMKN 3 Malang, SMKN 6 Surabaya and SMKN 8 Surabaya. This research uses research design with mixed method descriptive quantitative and qualitative to answer the above questions. Quantitative data analysis uses percentage, while qualitative data analysis uses triangulation data resources. The result of this research shows that (1) Curriculum conformity level according to the need of DU/DI in hair aspect at productive training education subject at SMK in Malang and Surabaya are : curriculum of SMKN 3 Malang with code A = 47,84%, curriculum of SMKN 6 Surabaya with code B = 49,84% and curriculum of SMKN 8 Surabaya with code C = 52,17%; (2) The demand of DU/DI for skill competence of hair beauty subject amount 14 competences; (3) The implementation of curriculum of productive training education lesson of hair beauty subject at each vocational high school in Malang and Surabaya involving the same curriculum document among the three vocational schools come from SKNI, for there devolepment are not the same because they are conformed with each school?s needs, KTSP of each schools are mostly added by local materials, SKL are the same, Silabus are different, conformed with local condition, from RPP have all been done, just only the division of learning hours should be more compacted at grade 1 and 2; (4) For technology developments, the student are demanded to study more, to practice more related with unfit competence that DU/DI demands, that is haircut and hair curling. Keywords: Curriculum, Business World/Industry World.